Physical geology - Plummer, Charles C.; Carlson, Diane H.; Hammersley, Lisa (McGraw Hill, 2022)
Physical Geology is a classic introductory text that has helped countless students learn basic physical geology concepts for over 25 years. Students taking introductory physical geology to fulfill a science elective, as well as those contemplating a career in geology, will appreciate the accessible writing style and depth of coverage in Physical Geology.